KOMUNIKASI ANTAR PRIBADI ORANG TUA DENGAN ANAK HUMBLEBRAG DI MEDIA SOSIAL - Andriani, Yesi; Romli, Nada Arina (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2022)
Interpersonal communication between parents and humblebrag children on social media. Introduction: Humblebrag is a behavior of someone who posts something good in the form of goods or activities that are being done on social media to show off but in a veiled way. If not addressed properly this humblebrag behavior can have a negative impact on children. Theory and Methods: This study uses the symbolic interaction theory and phenomenology and uses qualitative research methods. Result: interpersonal communication between parents and children about the humblebrag phenomenon is very necessary to instill an attitude of empathy to children and so that children do not like to show off on social media